2008
DOI: 10.1212/01.wnl.0000313376.07248.28
|View full text |Cite
|
Sign up to set email alerts
|

Occipital Levels of Gaba Are Related to Severe Headaches in Migraine

Abstract: Although GABA has figured prominently in theories of migraine pathogenesis, 1 brain levels of this transmitter have not been directly measured in migraineurs. This is of importance since, in migraine, neurophysiologic events account for brain hyperexcitability and subcortical disinhibition. 2,3 Magnetic resonance spectroscopy (MRS) measures levels of metabolites in the human brain and may map regional changes in their levels. 4 Accordingly, herein we used MRS to measure the levels of GABA in individuals with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 6 publications
2
38
3
Order By: Relevance
“…The results of post‐hoc analyses, showing no statistically significant correlation between GABA+ concentration and headache severity, differ from those of an earlier report indicating lower GABA levels in individuals with migraine with severe headaches . We believe that this difference in findings may be explained by the lack of variability in headache intensity of our participants (Table ).…”
Section: Discussioncontrasting
confidence: 99%
“…The results of post‐hoc analyses, showing no statistically significant correlation between GABA+ concentration and headache severity, differ from those of an earlier report indicating lower GABA levels in individuals with migraine with severe headaches . We believe that this difference in findings may be explained by the lack of variability in headache intensity of our participants (Table ).…”
Section: Discussioncontrasting
confidence: 99%
“…Drugs GABA agonist such as valproate and topiramate are very effective in the preventing the migraine without aura attacks [49]. However, direct evidence of GABA-related abnormalities in migraine is poor [50]. One study has shown that plasma levels of GABA increase at the end of migraine attack.…”
Section: Gaba and Migrainementioning
confidence: 99%
“…The implication of GABA in the pathogenesis of migraine is supported by several biochemical, pharmacological, neurophysiological, and experimental data, that are summarized in the Table (data included in this table were selected from those obtained through a PubMed Search crossing the terms “migraine” with “GABA” or “gamma‐aminobutyric acid” from 1966 to March 15, 2017, that retrieved a total of 271 references).…”
Section: Biochemical Pharmacological Neurophysiological and Experimentioning
confidence: 99%
“…9 Bridge et al 10 reported decreased GABA levels in the occipital cortex of 13 females with migraine with visual aura patients when compared with 13 female controls. Bigal et al 11 found no significant differences in occipital GABA levels between migraineurs (9 with and 10 without aura) and controls, or between patients with migraine with or without aura, although they found a trend toward lower GABA concentration in individuals with severe headaches in the previous month. Kono et al 12 found a significant decrease in 11 C-flumazenil binding (a marker of GABA A receptors) in the cerebellum of 3 patients with familial hemiplegic migraine type 1 associated with the CACNA1A gene mutation compared with the normal controls.…”
mentioning
confidence: 93%